ANALISA KANDUNGAN KADAR LOGAM BERAT PADA DAGING KEPITING (Scylla serrata) DI PERAIRAN MUARA SUNGAI BANYUASIN - Satria Rio Sandro; Susi Lestari; Anna Ida Sunaryo Purwiyanto (Universitas Sriwijaya, 2013)
Heavy metal was a pollutant because its stable and difficult to disentangle. Heavy metals in the waters of Banyuasin’s estuaries alleged negative impact on crabs and other aquatic animals. To see the impact research on the analysis of heavy metal content in the crab (Scylla serrata), in the territorial waters of Banyuasin’s estuaries. The objective of this study was to determine the content of heavy metals (Pb, Cu and Fe) in the crab meat (Scylla serrata) in the territorial waters of Banyuasin’s estuaries. Completely randomized design was used with 3 stations treatment and each station was repeated 3 times. Parameters observed were lead (Pb), copper (Cu) and iron (Fe).The results showed that the content of lead (Pb), copper (Cu) and iron (Fe) were different at each station.The highest content of lead (Pb) was on SI 0.0073 ppm and the highest content of copper (Cu) was on S-III 0.3713 ppm. The result indicates that still safe the crab (Scylla serrata) to consume based on national standards Pb 0,5 mg/kg and Cu 20 mg/kg . Iron content exceeds the standards set by the Department of Health in S-II at 2.054 ppm. Results of analysis of the iron content (Fe) on crab meat in consumption should be limited according to the established standards 2 mg/kg.